Study of pest attacks on maize plantation in the oil palm replanting land of Jambi Province. Issue 1 (April 2021) - Meilin, A; Rubiana, R; Jumakir,; Suheiti, K; Murni, WS; Rustam,; Bobihoe, J
Abstract: Activities of oil palm rejuvenation started in 2017 in Jambi Province. On replanting land, oil palms were intercropped with food crops (maize) while waiting for oil palm yield. Some constraints of food crop cultivation, including corn, is a pest attack. This study aims to determine the pest attack on maize plantations in oil palm replanting land. The research was conducted at maize plantation in oil palm replanting land in Talang Bukit and Marga Mulya Village, Sungai Bahar District, Muaro Jambi Regency from April to July 2019. This research used survey methods with 1 to 2 ha areas in each location during the maize's vegetative and generative phases. Morphology or symptoms of the attack, pest morphology, and the percentage of pest attacks observed in this study. The research result showed that the primary pest attacks in the maize's vegetative phase were Spodoptera frugiperda Fall Armyworm, which attacks the percentage reaching 93.45%, and then Spodoptera litura Armyworm, and Mythimna separata . Pest attacks at the generative phase of corn plants were S. frugiperda, S. litura, Rhopalosiphum maidis aphids, Ostrinia furnacalis stem borer, Helicoverpa armigera, respectively is 23.92%; 10.14%; 0.27%; 21.22%; 34.23%. Meanwhile, the damage caused by wild boars reached 27.56%, and 5.68% showed by the monkey.